Diseño desde una olla: repensando las realidades entre los paradigmas de diseño, roles y la producción local - Ayala Andazabal, Claudia Lucía (2024)
This talk is part of the CAP Research Award Project “Olla del pueblo - Una perspectiva del diseño hacia las identidades e imaginarios populares” (Folks Pot: A design perspective towards the identities and popular imaginary). Said research project in development aims to identify and propose guidelines for product design based on understanding the sociocultural processes that products go through as part of popular scenarios. With the guidelines developed, it´s expected the promotion of critical analysis of designers´ roles towards the local culture and popular manifestations, revalorising them by considering relevance as part of current design processes. During the research, the team found different critical contact points between the ideas of the “design-taught person” (designer) and the local/ regional reality where objects/ products of various natures are made. The first idea occurs from a design paradigm promoted by an academy with a historically-based pedagogic method modelled after European canons (Bauhaus, Ulm). The second idea, attributed to an empirical result of different communities’ economic and sociocultural development, established across the region as one said result: artisanal products. This talk will show how this project, following processes related to fundamental research and creation-research in design, not only aims to guide development but also questions the paradigms established in Industrial Design. Ultimately, this project aims to elaborate possible models which allow integration between design, the region and what has been done even before the idea of design.